Line break situations in international rugby - Diedrick, E.; van Rooyen, M. (International Journal of Performance Analysis in Sport, 2011)
The team who scored the most tries won 81% of all Rugby World Cup matches in 2007. However, there is little research published into events that lead to tries being scored from open play and especially the line break situation. There were a total of 47 line breaks recorded during 11 matches, 51% of which resulted in a try being scored, 30% of which no try was scored but possession was retained and 19% resulted in possession being lost. Most of the line breaks occurred within the attacking half of the field (55%) with 45% occurring from within the defending half. 89% of line break situations occurred towards the centre and left side of the field in the midfield zones B and C. 68% of the line breaks were created by the winning teams and these originated predominantly from the middle and left channels of the attacking half of the pitch. Losing teams relied on interception line breaks for their tries. The players most frequently observed making the line breaks were the left wing (17%), the fullback (13%.) Line breaks were an effective source of tries with an average of 2 tries being scored from a line break every match.